Eschatological Failure as God’s Mystery: Reassessing Prophecy and Reality at Qumran and in Nascent Christianity - Ruzer, Sergʹ (Dead Sea discoveries, 2016)
The article discerns in both Qumranic sources and in those coming from the nascent Jesus movement responses to their shared experience of disappointment vis-à-vis postponement of the expected redemption. The discussion, focusing on 1QpHab and a number of New Testament epistles, highlights the usage in this context of the language of God’s mystery, standing for reinterpretation of redemption-centered prophecies and their adjustment to a new timetable. While no clear direct links can be posited, the comparative study of the texts independently penned within the two eschatological groups allows to single out an underlying more general late Second Temple religious pattern of coping with delay in the anticipated end-of-days deliverance.